Implementasi Pemahaman Konsumsi Islam Pada Perilaku Konsumsi Konsumen Muslim - Alkautsar, Zulfikar; Hapsari, Meri Indri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
People does consumption to fulfill their needs in order to keeping their life. There are guidelines in Islam telling how a Moslem is supposed to consumed. A Moslem needs a comprehensive understanding about Islamic consumption in order to adjust their consuming behaviour with Islamic syaria. The understanding causes an implication of Moslem consumer behaviour in daily life.This research uses case study method with descripive qualitative approach. Author uses interview for primary data collection in this research. The scope of this research is limited in student of Islamic Economics of Economics and Business Faculty of Airlangga University and answer how to implement Islamic consumption understanding in Moslem consumption behavior.The result of this research shows there are four elements of Islamic consumption which is used as a guideline for moslem while they do consumption, ie: halal products consumption, avoiding excessive consumption (israf), paying zakat, infaq, and charity, and making needs priority. The informen confess that there is a difference in their consuming behaviour beforeand after knowing the Islamic consumption theory.